Developing Kindergarten Teachers’ Computational Thinking Skills Through Song Creation - Rien Safrina; Helena E Limbong; R.M. Aditya Andriyanto (Proceeding International Conference on Digital Education and Social Science, 2024)
This research aimed to assist teachers in developing computational thinking skills through children's song creation. The study focused on the process of creating songs while integrating computational thinking elements such as decomposition, pattern recognition, abstraction, and algorithm. The study was conducted in 2024. Sixteen kindergarten teachers from Lab-school Jakarta participated in the research and were divided into four groups for the song-creation process. A development research method using the Borg & Gall procedural model was employed. Due to time constraints and the nature of the product, the research adapted the ten-stage development research procedure by condensing it into five steps: information gathering, initial draft planning and development, product testing, revision of test results, and dissemination and implementation. Data was collected through focus group discussions, observations, and documentation of the song creation process. Data Analysis used descriptive analysis using field notes, critical memos, coding, data reduction, and data display based on factual data and information, along with music analysis techniques . The results indicated that teachers could develop computational thinking skills through song creation. During the process, teachers could identify how decomposition, pattern recognition, abstraction, and algorithms were applied. The four songs produced by the teacher groups demonstrated the development of teachers' computational thinking skills. This research implies that teachers can enrich early childhood learning approaches by adding a computational thinking dimension through music activities. Additionally, it provides recommendations for education in designing effective learning programs to develop computational thinking in young children.